Psychiatric drugs: reconsidering their mode of action and the implications for service user involvement. Issue 1 (3rd May 2019) - Roberts, Marc
Abstract : Purpose: The purpose of this paper is to examine two competing pharmacological models that have been used to understand how psychiatric drugs work: the disease-centred model and the drug-centred model. In addition, it explores the implications of these two models for mental health service users and the degree to which they are meaningfully involved in decisions about the use of psychiatric drugs. Design/methodology/approach: The approach is a conceptual review and critical comparison of two pharmacological models used to understand the mode of action of psychiatric drugs. On the basis of this analysis, the paper also provides a critical examination, supported by the available literature, of the implications of these two models for service user involvement in mental health care. Findings: The disease-centred model is associated with a tendency to view the use of psychiatric drugs as a technical matter that is to be determined by mental health professionals. In contrast, the drug-centred model emphasises the centrality of the individual experience of taking a psychiatric drug and implies a more equitable relationship between practitioners and mental health service users. Originality/value: Although infrequently articulated, assumptions about how psychiatric drugs work have important consequences for service user involvement in mental health care. Critical consideration of these assumptions is an important aspect of seeking to maximise service user involvement in decisions about the use of psychiatric drugs as a response to their experience of mental distress.